Will small towns benefit? Expected COVID-19 pandemic-induced changes in supralocal relationships of Polish small towns and planned responses in the supralocal perspective of their local development strategic governance - Sztando, Andrzej (Czy małe miasta skorzystają? Spodziewane zmiany ponadlokalnych relacji polskich małych miast wywołane pandemią COVID-19 oraz planowane reakcje na nie w ponadlokalnej perspektywie zarządzania strategicznego ich rozwojem lokalnym, 2020)
The system transformation of the 1990s for the majority of Polish small towns (STs) meant deep, unfavourable changes in the supralocal conditions of their local development (LD). As a result, they were affected by many negative phenomena. The COVID-19 pandemic has started socio-economic changes, the current predominant assessment of which is negative. Nevertheless, for Polish STs, instead of short-term reworsening their supralocal situation, these changes may turn out to be beneficial in the longer term. The article presents the expectations and observations of authorities in the field of pandemic-induced changes in the relations between their STs and the supralocal environment, as well as the planned, strategic reactions. The results of the research allowed conclusion that the changes in question in combination with the planned reactions have a significant stimulating potential in terms of LD. The article ends with recommendations for the use of information contained in the post-pandemic strategic governance of STs, in creating anti-crisis policies of states and in teaching practice
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 10, s. 119-147